Clinical inflammatory shifts and peripheral flow-cytometry immune modules across benign pulmonary nodules, adenocarcinoma-spectrum nodules, and overt lung cancer - Yunwei Rao; Qianyue Gong; Jiawei Li; Nan Liu; Hongmei Miao; Jinyue Huang; Shuiming Xu (Frontiers in Immunology, 2026)
Objective Pulmonary nodules (PN) represent a clinically heterogeneous pathway that includes benign lesions, adenocarcinoma-spectrum lesions, and cases that may differ from clinically overt lung cancer (LC). This study aimed to define a peripheral blood immunophenotyping framework for this pathway by integrating routine inflammatory readouts with transparently defined whole-blood flow-cytometry immune modules. Methods We performed a retrospective analysis of a single-center locked cohort of 217 participants, including healthy controls (n=121), pulmonary nodules (n=46), and overt lung cancer (n=50). The PN group was further stratified into benign PN (n=20) and adenocarcinoma-spectrum PN (n=26). Clinical readouts included neutrophil-to-lymphocyte ratio (NLR), systemic immune-inflammation index (SII), albumin, and lymphocyte measures. Peripheral immune phenotypes were summarized using four code-defined flow-cytometry module scores: B-cell remodeling, Tfh/Th2 skew, cytotoxic attenuation, and CD28-loss. Group differences were evaluated using Cliff’s delta with 95% confidence intervals and FDR-adjusted q values, with adjusted models used only as supportive diagnostics. Results Within the PN cohort, adenocarcinoma-spectrum PN showed a coherent inflammatory and lymphocyte-axis shift relative to benign PN, including higher NLR (delta=0.70, q<0.001), higher SII (delta=0.62, q<0.001), higher inflammation score (delta=0.81, q<0.001), lower albumin (delta=-0.69, q<0.001), and lower lymphocyte percentage (delta=-0.72, q<0.001). In the peripheral immune layer, overt LC showed higher module scores than PN across B-cell remodeling (delta=0.38, q=0.002), Tfh/Th2 skew (delta=0.40, q=0.001), cytotoxic attenuation (delta=0.47, q<0.001), and CD28-loss (delta=0.27, q=0.021). Focused and sensitivity comparisons preserved the direction of the module findings, with the strongest support for cytotoxic attenuation and Tfh/Th2 skew. Conclusion This study provides a clinically anchored description of peripheral inflammatory and immune patterns across clinically defined PN and overt LC groups. The findings identify inflammatory heterogeneity within PN and higher immune-module scores in overt LC, providing a hypothesis-generating framework for prospective validation and paired tissue-peripheral studies.